1986
DOI: 10.1038/320758a0
|View full text |Cite
|
Sign up to set email alerts
|

Binding of angiotensin and atrial natriuretic peptide in brain of hypertensive rats

Abstract: Atrial natriuretic peptides, produced in the mammalian cardiac atrium, are released into the general circulation and may be actively involved in the control of blood pressure and in fluid homeostasis as antagonists of the peripheral angiotensin system. Certain cardiovascular effects of atrial natriuretic peptides may be centrally mediated, as binding sites for atrial natriuretic factor (8-33) (ANF) have been localized to the subfornical organ. This circumventricular structure lacks a blood-brain barrier and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
2

Year Published

1987
1987
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(44 citation statements)
references
References 34 publications
1
41
2
Order By: Relevance
“…Mammalian atria contain different peptides, including the atrial natriuretic factor (ANF), that possess potent diuretic, natriuretic, and vasoactive properties (1,2). ANF is released into the general circulation and has been proposed to be actively involved in blood-pressure regulation and fluid homeostasis as an antagonist of the renin-angiotensin (Ang) system through receptor-mediated actions in the kidney (3), vascular tissues (4), adrenal glands (5), and brain (6). In the brain, binding sites for ANF have been characterized in specific areas involved in blood-pressure control, such as the subfornical organ (7)-a circumventricular structure that lacks the tight capillary endothelial junctions of the blood-brain barrier and, therefore, is exposed to circulating peptides.…”
Section: S-smentioning
confidence: 99%
“…Mammalian atria contain different peptides, including the atrial natriuretic factor (ANF), that possess potent diuretic, natriuretic, and vasoactive properties (1,2). ANF is released into the general circulation and has been proposed to be actively involved in blood-pressure regulation and fluid homeostasis as an antagonist of the renin-angiotensin (Ang) system through receptor-mediated actions in the kidney (3), vascular tissues (4), adrenal glands (5), and brain (6). In the brain, binding sites for ANF have been characterized in specific areas involved in blood-pressure control, such as the subfornical organ (7)-a circumventricular structure that lacks the tight capillary endothelial junctions of the blood-brain barrier and, therefore, is exposed to circulating peptides.…”
Section: S-smentioning
confidence: 99%
“…Further, their parenchyma is composed of glial and neuronal networks including small nerve cell somata, dendritic and axonal processes as well as terminals (Weindl et al, 1992). In addition, these CVOs have been reported to contain binding sites for several circulating substances, such as steroid hormone (Stumpf et al, 1992), angiotensin II and atrial natriuretic peptide (ANP) (Saaverdra et al , 1986;Skofitsch and Jacobowitz, 1988;Ferguson., 1992), which can not physiologically penetrate the brain tissues. In mammals, neutral glycoproteins have generally been presumed to function by recognizing cells and physiologically active substances and by receiving chemical informations (Hughes, 1975;Shinohara, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that ANF and angiotensin II may act as physiological antagonists in the brain, as in the periphery, 3 u and that the actions of ANF within the brain are well coordinated with its peripheral actions to regulate blood pressure and electrolyte and fluid homeostasis. 13 This idea is supported by recent findings that centrally administered ANF inhibits angiotensin II-induced water drinking, 33 -M salt appetite, 35 vasopressin secretion, 36 -37 and corticotropin (ACTH) secretion 38 ; antagonizes the centrally, but not intravenously, angiotensin II-induced increase in blood pressure 39 ; and potentiates the hypotensive action of the angiotensin blocker saralasin in SHR.…”
Section: Discussionmentioning
confidence: 99%
“…40 In the subfornical organ of the brain, a much lower number of ANF receptors was found in SHR than in normotensive controls, 11 whereas the number of angiotensin II binding sites was higher in SHR, as compared with WKY. 3 The subfornical organ contains one of the highest concentrations of ANF receptors 2 -4 as well as angiotensin II receptors 41 in the brain and has long been implicated in the central control of body fluid homeostasis and blood pressure. 42 - 43 It has been demonstrated to be one of the main target sites for circulating angiotensin II 44 - 45 and could mediate the central actions of circulating ANF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation